2018
DOI: 10.31234/osf.io/7t9xd
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neural predictors of eating behavior and dietary change

Abstract: Recently, there has been an increase in the number of human neuroimaging studies seeking to predict behavior above and beyond traditional measurements such as self-report. This trend has been particularly notable in the area of food consumption, as the percentage of people categorized as overweight or obese continues to rise. In this review, we argue that there is considerable utility in this form of health neuroscience, modeling the neural bases of eating behavior and dietary change in healthy, community popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…Second, to make the task feasible in our lab environment, we assessed appetitive reactivity using food pictures and self-report, which may yield different or weaker results compared to measurements involving the presence of real food and subsequent food consumption (e.g. see Giuliani, Merchant, Cosme, & Berkman, 2018). Third, the first cohort of adults we tested did not complete the full battery of individual difference measures and as a result we may have been underpowered to detect group-level differences in relationships between these measures and social influence.…”
Section: Discussionmentioning
confidence: 99%
“…Second, to make the task feasible in our lab environment, we assessed appetitive reactivity using food pictures and self-report, which may yield different or weaker results compared to measurements involving the presence of real food and subsequent food consumption (e.g. see Giuliani, Merchant, Cosme, & Berkman, 2018). Third, the first cohort of adults we tested did not complete the full battery of individual difference measures and as a result we may have been underpowered to detect group-level differences in relationships between these measures and social influence.…”
Section: Discussionmentioning
confidence: 99%
“…Realignment parameters were transformed into Euclidean distance for translation and rotation separately, and we included the displacement derivative of each. Another "trash" regressor marked images with motion artifacts (e.g., striping) identified via automated motion assessment (Cosme et al, 2018) and visual inspection. Eight participant task runs were excluded from the group-level analysis for having >10% of volumes contaminated with motion artifacts, which was more than 4 SD from the median (Mdn = 0.40%, SD = 2.29%).…”
Section: Supplementary Materials Fmri Acquisition Preprocessing and mentioning
confidence: 99%
“…We were particularly interested in examining engagement of multiple cognitive processes when participants were exposed to high-calorie, appetizing food items during an fMRI scanning session. We adopted a framework recently proposed by Giuliani and colleagues (2018) that posits three fundamental processes at play during food cue exposure that guide subsequent eating behavior: reactivity, regulation, and subjective valuation, with specific neural systems supporting each process (Giuliani et al, 2018). We aimed to determine the extent to which: (1) brain regions associated with these processes, absent any instructions to regulate or alter their cravings, are variably recruited person to person; and (2) whether individual differences in activation patterns indexing these processes are reliably associated with body composition and daily eating behaviors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Neuroimaging research has focused on the cue-reactivity paradigm (2), an experimental procedure involving the examination of neurofunctional responses to the controlled exposure to stimuli (foodor drug-related) inducing craving, namely the strong and intense desire to seek and consume a substance. These studies have revealed a distributed network of brain regions recruited during exogenous (i.e., perceptual food pictures, odors or tastes) and endogenous (i.e., imagery) cue-reactivity (see (3) for review and(4, 5) for meta-analyses).…”
Section: Introductionmentioning
confidence: 99%